Comparison of Musculoskeletal Disorder Risk based on Gender in High School Students - Lestari, Putri Winda; Purba, Yunita Sari; Tribuwono, Agung Cahyono (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
In Indonesia, there is a tendency for the emergence of musculoskeletal disorders (MSDs) in school-aged children. MSDs can cause disruption of daily activities, such as lost school time. Individual factors such as sex can be the cause of MSDs. This study aims to determine how much gender differences affect the risk of musculoskeletal disorder. The design of this research was analytic observative with cross-sectional approach. The population is all high school students in the Kec. Kramat Jati East Jakarta as many as 4,708 students. The research sample was 370 class XI students. Samples were taken by simple random sampling. The independent variable is gender while the dependent variable is MSDs. Retrieval of data by filling out the Nordic Body Map questionnaire. Data were processed univariately and bivariately with chi-square test. The results showed that there was a relationship between sex and musculoskeletal disorder. The value of p = 0,000 with a PR value = 1,131 and 95% CI = 1,051 - 1,217 which shows that female are more at risk 1,131 times having musculoskeletal disorder compared to male.